Prevalence and Situation of Clients with Celiac Disease in the Zliten Area: A Comprehensive Study - Miftah Khaleel Alati (Sharwes Scientific Journal, 2025)
The study aimed to know the prevalence of celiac disease (CD) among people who lived in the Zliten Area and study the conditions of CD patients, and relied on a descriptive and analytical approach. The data collected were from people who had a celiac disease using a questionnaire to collect personal parameters and link it with how strict the patients are with following a gluten-free diet (GFD), the price of gluten-free food (GFF), availability, and variety of GFF. There were 439 respondents, the data by SPSS (version 23.0, 2015). The data subjected were to a one-way analysis of variance (ANOVA) at p≤ 0.05. The result showed that the celiac patient ratio in the Zliten area was 1:683. The female-to-male ratio was 2:1. The majority of celiac cases were mostly children. 91.1% of the study subjects strictly followed GFD. 90.9% of the respondents claimed that the price of GFF was very high. 98.2% of cases could find GFF only in especial groceries; moreover, 92.3% of study subjects did not find a types variety of GFF, and 69.8% did not get GFF regularly. There was a significant difference between ages, genders, and education levels concerning the following GFD. Subsequently, the study recommends that more care should be taken for clients with celiac disease, as more variety and enough GFF should be available at a suitable price.